Herd size, distribution, harvest, management issues, and research priorities relevant to caribou herds in Alaska - Valkenburg, Patrick (Rangifer, 1998)
There are presently about 960 000 caribou in 32 herds in Alaska, including 4 herds shared with Yukon and Northwest Territories. Since complete population data were last published in the mid-1980s, Alaska's caribou population has doubled in size, largely from increases in the Western Arctic and Mulchatna herds. The number of recognized herds has increased by 6, largely because of increased use of radiotelemetry to inventory small caribou herds in inaccessible areas, and transplanting caribou to unoccupied ranges. About 33 000 caribou are harvested annually in Alaska, mostly from the Western Arctic, Mulchatna, and Nelchina herds. The primary wildlife management problem in Alaska for caribou and other species is the lack of clear management authority among state and federal agencies. Research priorities include work on the influence of short-term and long-term weather trends on nutritional ecology of caribou, and predation mitigation including sterilization, translocation, and diversionary feeding of wolves during the caribou calving period.